The Landscape of Current Cloud Accounting Research: A Systematic Literature Review - Rodhiyah, Indah; Kesuma, Sambas Ade; Nasution, Fahmi Natigor; Erwin, Keulana (Jurnal EMT KITA, 2026)
This study systematically maps the recent cloud accounting literature, focusing on adoption factors, impacts on organizational performance, analytical technology implementation, and the theoretical frameworks and methodologies used in research conducted from 2024 to 2025. This study uses a Systematic Literature Review (SLR) guided by the PRISMA protocol. Data sources were obtained from the Scopus database using the single search string "cloud accounting" applied to Title/Abstract/Keywords fields. A total of 202 articles were identified and screened in stages based on publication year (2024-2025), document type, publication status, language, open access, and journal quality (Q1-Q4 based on Scimago Journal Rank). The selection process resulted in 16 final articles indexed in quartiles (Q1: 2 articles; Q2: 3 articles; Q3: 9 articles; Q4: 2 articles). Key findings are: (1) technological (security, compatibility, IT infrastructure), organizational (readiness, management support, employee capability), and environmental (stakeholder pressure, regulation) factors determine adoption; (2) cloud accounting enhances financial reporting quality, strengthens internal control, and curbs creative accounting; (3) analytical algorithms (k-Means, ID3, CAP, IGOA-KELM) are increasingly applied to support more intelligent financial decision-making. (4) Technology Acceptance Model (TAM) and Technology-Organization-Environment (TOE) frameworks dominate theoretical approaches, with Structural Equation Modeling (SEM) as the primary analytical method. This study provides a comprehensive synthesis integrating three previously fragmented research streams (adoption, impact, analytics) and offers practitioners evidence-based guidance for cloud accounting implementation, while identifying critical research gaps for future investigation.